LIVING HADIS GERAKAN ANTI-VAKSIN ASTRAZENECA DAN RELEVANSINYA DENGAN HADIS DI MEDIA SOSIAL - Mohammad Fattahun Niam (IAIN Syekh Nurjati Cirebon, 2022)
The anti-vaccine movement occurred in Indonesia. In the midst of the Covid-19 outbreak, there was an action against the Astrazeneca vaccine because it contained pork. The Indonesian Ulema Council issued a fatwa on the prohibition of the vaccine, but it may be used. This living hadith research uses the social construction theory of Peter L. Berger to reveal the meaning of the anti-vaccine movement through three stages of externalization, objectivity, and internalization. This paper reveals the public’s reception of hadith from the perspective of the sociology of knowledge. People’s reactions to the use of these vaccines are different. The antivaccine movement appeared on social media as a reaction to the illegal use of the Astrazeneca vaccine.